Abundant microchondrules in 162173 Ryugu suggest a turbulent origin for primitive asteroids - Matthew J. Genge; Natasha V. Almeida; Matthias van Ginneken; Lewis Pinault; Tobias Salge; Penelope J. Wozniakiewicz; Hajime Yano; Steven J. Desch (Nature Communications)
Abstract Chondrules are a characteristic feature of primitive Solar System materials and are common in all primitive meteorites except the CI-chondrites. They are thought to form owing to melting of solid dust aggregates by energetic processing within the solar nebula and thus record fundamental processes within protoplanetary disks. We report the discovery of abundant altered microchondrules (>350 ppm) with modal sizes of 6–8 µm within sample A0180 from C-type asteroid Ryugu. These microchondrules have similar log-normal size and shape distributions to normal-sized chondrules, implying evolution by similar size-sorting. We suggest here formation of microchondrules in an outer Solar System chondrule factory, located in the Jovian pressure-bump, followed by turbulent diffusion and concentration relative to chondrules by intense turbulence. Meridional flows could have also separated microchondrules from chondrules and deliver them sunwards of the pressure bump via Lindblad torque flows. Contrary to conventional wisdom we thus propose that the concentration of fine-grained, unprocessed grains could mean the most primitive asteroids did not have to form at the largest heliocentric distances.